Numerical study of gas bubbles collective dynamics in the melt influenced with magnetic field - Jakovics, A; Pavlovs, S; Baake, E; Steinberg, T; Sushkovs, V; Tatulcenkovs, A (HAL CCSD, 2015)
International audience The paper presents numerical study of methane (CH4) bubbles flow through molten tin (Sn) in electromagnetic (EM) field for cylindrical bubble reactor, which produces hydrogen (H2) without carbonic acid (CO2) emission.Eulerian-Eulerian approach, realized in commercial packages ANSYS CFX and ANSYS Fluent, as well as Boltzmann approach, realized as own code, are used for multiphase flow – liquid metal (continuous phase) and gas bubbles (dispersed phase). Magnetic field is uniform.Transient distributions of methane flowing in liquid tin, influenced with magnetic field, are discussed.